Sildenafil in the treatment of pulmonary hypertension - Barnett, Christopher F (Dove Medical Press, 2006)
The therapy of pulmonary hypertension has evolved rapidly in the last 10 years from the use of non-selective vasodilators to drugs that specifically target pulmonary vasodilation, endothelial function, and vascular remodeling. Sildenafil is a phosphodiesterase type 5 inhibitor that has an expanding role in the treatment of pulmonary hypertension. Case series and small studies, as well as the first large randomized controlled trial, have demonstrated the safety and efficacy of sildenafil in improving mean pulmonary artery pressure, pulmonary vascular resistance, cardiac index, and exercise tolerance in pulmonary arterial hypertension. It may be useful in adults, children, and neonates after cardiac surgery, with left heart failure, in fibrotic pulmonary disease, high altitude exposure, and thromboembolic disease, and in combination with other therapies for pulmonary hypertension, such as inhaled iloprost. The oral formulation and favorable adverse effect profile make sildenafil an attractive alternative in the treatment of selected patients with pulmonary hypertension.